Better together - George, K. (Kallie), 1983- (George, K. (Kallie), 1983- Heartwood Hotel, 2018)
Spring is here and the animal staff at the Heartwood Hotel are busy arranging a series of festivals and competitions to drum up business and to show its patrons that Heartwood is the greatest hotel in Fernwood Forest.